KOMODIFIKASI PERNIKAHAN REMAJA PADA SINETRON PENGANTIN DINI DI ANTV - Umi Septia Rahayu; Mulharnetti Syas (Jurusan Ilmu Komunikasi Universitas Andalas, 2020)
This study aims to examine the commodification of adolescent marriages in the Early Bridal soap opera on ANTV. The method used in this study is the semiotic analysis of the Rolland Barthes model with a qualitative approach. This study uses the constructivism paradigm as a research basis for in-depth how ANTV constructs adolescent marriage. This type of research is descriptive. This type of research aims to make a systematic, factual and accurate description of the facts contained in the soap opera of Pengantin Dini and to describe the reality that is built and commodified by ANTV. The theory used in this study is the Vincent Moscow Commodification Theory. In the results of text analysis using the Rolland Barthes semiotic method, ANTV describes married couples who have been married since adolescence as couples who are easily quarreled, mentally immature, and not ready economically, often parents who determine the way out of their children's problems, and students SMA can get married and continue to take formal education. The commodification of teenage marriage content in the Early Bridal soap opera on ANTV, the author of the analysis, is adolescent marriage that is filled with conflict and drama so that it is in demand by the public and has a sale value. This can be seen from the many advertisements embedded in the soap opera shows in various formats, such as running text and squeeze frames.